Influencing factors of driver’s habits and behavior: comparison between young and ageing populations - Abd Rahman, Nurul Izzah; Md Dawal, Siti Zawiah; Yusoff, Nukman (Korean Institute of Industrial Engineers, 2024)
The main aim of this study is to investigate the significant factors influencing driver’s habits and behavior across age groups. As ageing population is increasing rapidly, various age ranges of drivers on the roads require crucial awareness to better educate, manage, and restrain road behaviors. Driving is a complex task in ergonomics perspective that involves human, vehicle and environment. These factors have either advantageous or adverse impact on driving performance. It is crucial to identify and specify requirements necessary for a safe and efficient conduct of driving task. For changes in driving method or design to take place, both young and ageing drivers’ driving tasks need to be examined. Survey on drivers was conducted on 182 drivers (both genders). Participants was divided into two age groups: below 50 years is Younger Group; 50 years and above is Ageing Group. Validated questionnaires used in the study were 1) Driving Habits Questionnaire (DHQ) to evaluate current driving status, general driving practices, driving exposure, dependence on other drivers, and driving difficulty, and 2) Driver Behavior Questionnaire (DBQ) to assess errors, ordinary violations, lapses and aggressive violations. Most of the drivers had difficulty driving in the rain. More than half of the young and ageing drivers reported difficulty driving at night. Failure to notice that pedestrians were crossing was the most frequent error among young and ageing drivers. Age was significantly associated with driving preference during these conditions, rain, right turn in traffic, heavy traffic, rush hour and night driving and have effects on distractions, violations, errors, and lapse of drivers. The presented outcome highlighted the need to design and perform real-time driving experiment observing the on-road driving performance adopting the main elements examined in this study into the task to be assigned.